2017
DOI: 10.1007/s10461-017-1680-2
|View full text |Cite
|
Sign up to set email alerts
|

Community-Based Accompaniment with Supervised Antiretrovirals for HIV-Positive Adults in Peru: A Cluster-Randomized Trial

Abstract: We conducted a cluster-randomized trial to estimate effects of directly observed combination antiretroviral therapy (DOT-cART) on retention with viral suppression among HIV-positive adults in Peru. We randomly allocated facilities to receive the 12-month intervention plus the standard of care, including adherence support provided through accompaniment. In the intervention arm, health workers supervised doses, twice daily, and accompanied patients to appointments. Among 356 patients, intention-to-treat analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Indeed, negative societal attitudes toward MSM and TW may contribute to the sexual risk factors described above in terms of cultural perceptions (e.g., connecting insertive sex roles with masculinity and reduced HIV risk), power dynamics (e.g., low condom use due to forced sex and power dynamics with heterosexual-identified partners and/or socioeconomically affluent clients), and limited culturally astute healthcare centers (36). Second, studies have shown wide variation in mental health among Peruvians living with HIV (e.g., 7–49% of samples with depressive symptoms; 40, 41, 42). These high rates underscore the importance of identifying determinants of mental health problems among Peruvian PLWH.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, negative societal attitudes toward MSM and TW may contribute to the sexual risk factors described above in terms of cultural perceptions (e.g., connecting insertive sex roles with masculinity and reduced HIV risk), power dynamics (e.g., low condom use due to forced sex and power dynamics with heterosexual-identified partners and/or socioeconomically affluent clients), and limited culturally astute healthcare centers (36). Second, studies have shown wide variation in mental health among Peruvians living with HIV (e.g., 7–49% of samples with depressive symptoms; 40, 41, 42). These high rates underscore the importance of identifying determinants of mental health problems among Peruvian PLWH.…”
Section: Introductionmentioning
confidence: 99%
“…DOT for HIV has yielded mixed findings among adults [ 43 , 44 ], but ALWH found DOT supportive training for independent ART adherence rather than observed verification of medication ingestion; shifting to teledot did not change this viewpoint. The favourable view of HIV teledot corroborates a study among Peruvian adults with HIV reporting perceived psychosocial outcomes as the primary benefit of DOT [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…This was a nested study in the randomized-control trial community-based accompaniment with supervised antiretrovirals (CASA), which applied the community-based intervention of DOT to support PLWHA beginning ART. 9 The CASA cohort was composed of 356 participants living in poverty, who were enrolled between November 2010 and March 2012, within 30 days of ART initiation. Participants were at least 18 years of age, starting a new combined ART regimen, residing and receiving HIV care within 10 defined districts in Lima (selected from a total of 45 districts based on high prevalence of HIV), and amenable to receiving CHW visits for DOT.…”
Section: Methodsmentioning
confidence: 99%